Parapsykologit : ulkopuolisen näkemys poikkeavan tieteen suomalaiseen historiaan - Aho, Jouko (Historiallisia tutkimuksia, 1993)
Abstract: The parapsychologists : a history of a deviant science in Finland from an outsider's point of view.
Keywords: historia; parapsykologi; parapsykologia; Finland; Suomi